The communication between nursing team and the families of intensive care patients: qualitative study. - Sabrina Guterres da Silva; Adelina Giacomelli Prochnow; José Luís Guedes dos Santos; Soeli Teresinha Guerra; Sueli Gói Barrios (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <w:LsdException